CHRONIC MUSCLE WEAKNESS IS ACCOMPANIED BY PROLONGED OXIDATIVE DAMAGE IN MURINE SEPSIS SURVIVORS. (11th November 2018) - Steele, A; Mori, S; Balasuriya, B; Starr, M; Saito, H
Abstract: Aging is a predominant risk factor for developing sepsis, a serious life-threatening condition initiated by an uncontained infection. Elderly sepsis survivors commonly develop weakness which often causes previously independent individuals to be discharged to nursing care facilities. Such sepsis-induced physical dysfunction persists for years, and the mechanism is not currently understood. The objective of this study was to determine if chronic muscle weakness occurs in murine sepsis survivors and to evaluate protein oxidative damage as an underlying mechanism. Using our recently developed ICU-like resuscitation model of experimental sepsis (PMID 2787956) in late-middle-aged (16-month-old) mice, we found that mice have prolonged muscle weakness. In this study, experimental sepsis was induced, body composition was evaluated regularly, and mice were euthanized two-weeks and one-month after sepsis to assess skeletal muscle strength ex vivo. Muscle weakness was observed in the post-sepsis animals where the maximum specific force was 24.5% lower than non-sepsis controls at two-weeks after septic insult (p<0.01), and similarly at one-month (28.1% reduction; p<0.01). Animals lost 6.5 ± 0.9% of lean mass during sepsis (p<0.01) by day 4, which began recovering by day 7 (3.9%) and recovered by day 10 (p=0.3). Both nitro-oxidative damage and protein carbonyls were significantly elevated in the muscles of sepsis survivors at two-weeks (p<0.01 for both markers) and one-month (p<0.01, p<0.05 respectively) after sepsis. These data suggest that sepsis survivors have poor muscle quality which is associated with reduced muscle function, even after recovery of muscle mass. Therefore, antioxidant therapies may be effective treatments for sepsis-induced muscle weakness.